182k views
0 votes
Noah started to solve the equation –4.6p – 6.3p + 3.9 = –9.18 below. Combine like terms: –10.9p + 3.9 = –9.18 Apply the next steps to solve the equation. What is the solution? p =

User Shai Alon
by
5.1k points

2 Answers

4 votes

Answer: p= 1.2

Step-by-step explanation: I got it right

User Carl Thomas
by
5.9k points
4 votes

Answer:

The value of p = 1.2

Explanation:

-4.6p – 6.3p + 3.9 = –9.18

Combine like terms

–10.9p + 3.9 = –9.18

Subtract -3.9 on both sides, we get

-10.9p + 3.9 -3.9 = -9.18 -3.9

-10.9p = -13.08

Dividing both sides by -10.9, we get

p = -13.08/-10.9

p = 1.2

The value of p = 1.2

Hope this will helpful.

Thank you.

User Mlishn
by
5.7k points